Body movement imitation and early language as predictors of later social communication and language outcomes: A longitudinal study. (June 2016) - Dohmen, Andrea; Bishop, Dorothy VM; Chiat, Shula; Roy, Penny
Background and aims: Over recent decades much research has focused on detecting predictors of different language trajectories in children with early language delay but there has been very little exploration of social communication trajectories in these children. We report a longitudinal study that investigated the predictive value and clinical significance of elicited body movement imitation and language for later social communication and language outcome in Late Talkers. Methods: Participants were 29 German-speaking children who were identified with delayed onset and progression of language at two years and followed up at four years. Novel assessments of posture and gesture imitation were administered at Time 1, together with standardised language measures. All body movement imitation items involved self-other mappings, assumed to rely on sociocognitive capacities. At Time 2, children were assessed on standard language tests, together with parental reports of social communication. Results: Early language skills at Time 1 were significantly associated with later language outcome and body movement imitation skills at Time 1 with later social communication outcome. Logistic regression analyses revealed that body movement imitation as well as language at Time 1 added significantly to the prediction of language outcome at Time 2, whereas only body movement imitation made a significant contribution to the prediction of social communication outcome at Time 2. Conclusions and implications: Theoretically, results highlight the need to account for the heterogeneity of different language and communication trajectories in children with early language delay and point to the importance of sociocognitive difficulties observed in some of these children. Clinically, this study demonstrated that body movement imitation measures have the potential to improve the identification of pre-schoolers who are at risk of later social communication and language problems.